Trade competitiveness and export performance of Indian cardamom - P C Sanil, L Thomas, P Rajeev, (Journal of Spices and Aromatic Crops, 2019)
India is one of the major producers and consumer of cardamom. The export performance of cardamom has witnessed several changes over the past few decades. This paper analyses the trends and performance of cardamom commodity from India. Using secondary data from the Spices Board and the Ministry of Commerce along with international trade data from the United Nations International Trade Statistics Database, the trend in the domestic production and export markets is clearly drawn out. The changes in Revealed Comparative Advantage in cardamom exports over the years is used to study the level and changes in the export competitiveness of the commodity. The study identifies a revival in export competiveness in the recent years along with an increase in the share of global cardamom exports. The highly concentrated production of cardamom, the preference for Indian cardamom in Middle East economies and the revival of export competitiveness can benefit the Indian cardamom producers. The study argues for strengthening research investments in cardamom for sustaining and enhancing the benefits from cardamom exports from the country.